2020
DOI: 10.1088/1742-6596/1482/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of ZnSe/InSe/ZnSe heterostructures grown by molecular beam epitaxy on GaAs(001) substrates

Abstract: The paper reports on molecular beam epitaxy of ZnSe/InSe/ZnSe quantum well (QW) heterostructures grown on GaAs(001) substrates as well as studies of their structural properties. The structures were characterized by reflection high energy electron diffraction, scanning electron microscopy, and high-resolution transmission electron microscopy techniques. The evolution of surface morphology of QW heterostructures as a function of the InSe thickness has been studied. The quasi van der Waals growth of ZnSe on the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, the orientation of the ZnSe layer remains unchanged in those parts of the structure where there are no InSe islands. The existence of the (111)-oriented ZnSe phase in the structure was also confirmed by SAED measurements [ 101 ]. We suppose that the growth of ZnSe with a (111) orientation onto the InSe(0001) van der Waals surface is caused by the proximity of the InSe and ZnSe(111) lattice parameters (Δa/a ~ 1% or less, a(InSe) = 4.005 Å [ 41 ]).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…However, the orientation of the ZnSe layer remains unchanged in those parts of the structure where there are no InSe islands. The existence of the (111)-oriented ZnSe phase in the structure was also confirmed by SAED measurements [ 101 ]. We suppose that the growth of ZnSe with a (111) orientation onto the InSe(0001) van der Waals surface is caused by the proximity of the InSe and ZnSe(111) lattice parameters (Δa/a ~ 1% or less, a(InSe) = 4.005 Å [ 41 ]).…”
Section: Resultsmentioning
confidence: 82%
“…The top ZnSe layer on the InSe surface was grown at T S = 300 °C. The details of MBE growth of ZnSe/InSe/ZnSe QW heterostructures as well as studies of their surface morphology were recently reported by Avdienko et al [ 101 ]. Here, we focus mainly on the structural and optical properties of these QW structures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations